The effect of NbC on mechanical properties and fracture behavior of WC–10Co cemented carbides. (May 2015) - Zhou, Wei; Xiong, Ji; Wan, Weicai; Guo, Zhixing; Lin, Zihao; Huang, Shiwei; Tang, Limei; Zhong, Hua
Abstract: In an attempt to improve the understanding of fracture behavior of brittle cemented carbides with NbC addition, a detailed study was conducted with the main goal of characterizing the fracture character and crack growth mode. The study showed that NbC had a significant influence on the mechanical properties of WC–10Co alloys. The maximum hardness and transverse rupture strength were observed when the NbC content was 1 wt.%. However, with the further addition of NbC, the TRS and fracture toughness degraded. The fracture origin was cleavage fracture from coarse WC when the addition of NbC was 1 wt.% and 2 wt.%. But in the materials with 3 wt.% and 4 wt.% NbC addition, the brittle (W, Nb)C solid solution increased considerably, and this leaded to a low stress brittle fracture. In the WC–10Co alloy, intergranular growth was the dominant mode of crack propagation. The ratio of transgranular crack increased because of the grain refinement of WC and solid strengthen effect of binder by NbC, and the transgranular crack in brittle (W, Nb)C solid solution increased when NbC content was increased to 3 wt.% and 4 wt.%. Highlights: The fracture character of WC–10Co–xNbC was studied in this paper. The fracture origin was cleavage fracture of coarse WC with a lower addition of NbC. Excessive transgranular brittle fracture of (W, Nb)C was observed when NbC was added in. The coarse (W, Nb)C made a degradation of crack growth resistance of WC–10Co–xNbC.